Classification of a Subclass of Two-Dimensional Lattices via Characteristic Lie Rings - Habibullin, I.; Poptsova, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
The main goal of the article is testing a new classification algorithm. To this end we apply it to a relevant problem of describing the integrable cases of a subclass of two-dimensional lattices.